PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK - DWI RATMAWATI; Dhiya Ayu Tsamrotul Ihtiari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2021)
The results of mathematics lessons of grade 4 students of MI Maarif Kapulogo Village, Kepil Wonosobo subdistrict can be said to be renddah. Based on the results of the interview obtained data on the average daily repeat value of students multiplication material and the division of numbers is 67.00 and students who can be said to complete is 6 students out of 10 students, then the percentage of completion of student learning is 62%. The research aims to know the process of mathematics learning and to know the improvement of learning outcomes in grade 4 students of MI Ma`arif Kapulogo Kepil Wonosobo in the 2020/2021 school year after learning using Talking stick learning models. This type of research is a class action research with 2 cycles and each cycle consists of 4 stages namely planning, implementation, observation and reflection. The subject of the study was a grade 4 student of MI Ma'arif Kapulogo with a total of 10 people. Collection using observation and test methods. Data analysis using descriptive analysis. The results showed that the mathematics learning process using Talking stick learning model in grade 4 students of MI Ma'Arif Kapulogo Kepil Wonosobo in the 2020/2021 school year was carried out as many as two cycles and each cycle consisted of 2 meetings. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The results showed that the average results of learning mathematics in pre-cycle was 57 with 50% completedness. Then the average results of learning mathematics in the cycle increased to 70 with 70% completeness and in the second cycle the average results of mathematics learning increased to 85 with 90% completeness. Thus, the learning model of Talking stick approach can improve the results of mathematics learning students in grade IV MI Ma'arif Kapulogo District Kepil Wonosono Regency